The role of family and culture in the development of emotional intellect - Jabbarova Telli Rahim, (Technium Social Sciences Journal, 2020)
The aim of the study is to determine the influence of family and culture on emotional intellect and to study the causes of various psychological factors. The methodological basis of the study is the relationship between cognitive and emotional factors in the behavior of individuals, theories and experiments related to emotional intellect. The scientific novelty of the research is the study of the influence of family and cultural environment on the development or weakening of emotional intellect. Output. Positive emotions that parents send to their children create conditions for the development of their emotional intellect, and negative emotions for lagging behind the level of emotional intellect. This, in turn, gives an impetus to the formation of certain psychological qualities in them. Social norms, gender and culture that play a role in the formation of the family environment are involved in the formation of the emotional intellect of the individual through the family. In a family, the emotional attitude of parents towards children and methods of emotional education influence the formation of the character of their future personality. Considering that people share their emotions mainly with close family members, we can say that the family is the main social mechanism that determines, directs and regulates the emotional state of society. The weakening and deterioration of this mechanism can lead to emotional imbalance in society. This is confirmed by the fact that young people belonging to criminal and deviant groups come mainly from disadvantaged families.